Protecting-Group-Free Synthesis of Novel Cannabinoid-Like 2,5-Dihydrobenzoxepines - Nguyen, Gia-Nam; Jordan, Erin Noel; Kayser, Oliver (Synthesis, 2022)
An efficient synthesis of 2,5-dihydrobenzoxepine analogues was developed without using protecting groups. Regioselective allylation was optimized through a recent method utilizing magnesium dicarboxylates. Grubbs catalysts were applied to investigate ring-closing metathesis. The scope of the present route was extended to produce four analogues, which provided novel cannabinoid-like 2,5-dihydrobenzoxepines in sufficient quantities to permit in vitro assays on recombinant CB1/CB2 receptors. In vitro assays related to CB1/CB2 receptors did not indicate any activity.
Keywords: 2,5-dihydrobenzoxepine; radulanin A; benzoxepin cannabinoids; regioselective allylation; ring-closing metathesis